Size effect on the martensitic transformation of Ti–Nb shape memory alloy. (June 2022) - Sun, Bin; Sun, Kuishan; Meng, Xianglong; Wang, Jun
Abstract: The effect of grain size on martensitic transformation was investigated by transmission electron microscopy in a nanocrystalline Ti–16Nb thin film with a broad range of grain sizes. The results show that the larger nanocrystals are filled with multiple variants with the 111 α " type I twinning relationship. As the grain size decreases to about 40 nm, the martensite changes to the single variant morphology, and the shape memory effect is believed to deteriorate significantly then. Finally, the martensitic transformation is totally suppressed and the β parent remains when the grain size drops below 25 nm. Highlights: Ti–Nb nanocrystalline thin film is fabricated by magnetron sputtering apparatus. The size effect on the martensitic transformation of Ti–Nb alloy is studied. The critical grain size for shape memory effect is about 40 nm. The martensitic transformation is suppressed when the grain size below 25 nm.